Med lokalnim in nacionalnim - Petrović, Tanja (Jezik in slovstvo, 2006)
Through analysis of the features of language used by members of the Serbian community living in the Bela krajina region, the author of this article shows how the language ideology predominant in modern European nations - where the standard and national language is the most prestigious means of communication and the monolingual situation is accepted as the only natural and desired state - has a vital impact on the perception of a language by its speakers andconsequently also on their communication strategies. This is particularly true of the speakers of minority and non-standard languages. In this context, an example of language replacement by the Serbs in Bela krajina, which has been going on intensely since the Second World War, can be treated as one of the illustrations of the process in which this local community is becoming part of wider, i.e. national social structures. Slovenia s integration into the European Union has hardly had an influence on the linguistic situation andthe direction of language replacement for the Serbs in Bela krajina (similar is true of other local linguistic communities in EU member countries), since in the European Union, regardless of its institutionalised orientation towards supra-national values, the ideology of standard languages remains predominant.
Keywords: Bela krajina; jezikovna identiteta; linguistics; lingvistika; Serbs; Slovenia; Slovenija; Srbi; White Carniola